Formigas e o Código Florestal Brasileiro : comparando Áreas de Preservação Permanente (APP) e Reserva Legal (RL) - Almeida, Rony Peterson Santos (2015)
The New Brazilian Forest Code (NCFB) presents some controversial points in its text, especially those related to the reduction or replacement of legal reserves (LRs) and Permanent Protection Areas (PPAs) for non-native vegetation or the compensation of these areas by another, on the same property. The NCFB therefore considers these two areas structurally similar and able to house and preserve the fauna and regional flora. This work aims to analyze the existence of similarity between LRs and PPAs, with focus on environmental complexity on the fragments and the use of ants as bioindicators. For this purpose, samplings were taken in six areas, three of them considered LR and three as PPA. In each area, one transect was subdivided into 30 plots of 5 x 5m and 6 m spaced. In each plot, we measured plant litter depth, density of trees and the canopy cover (%). Furthermore, in the central area of each plot, we toke a 1m² samples of plant litter to analyze the ant fauna. The relationship between ant richness and environmental variables were tested using generalized linear models (GLMS), and the species composition between areas was checked through non-metric multidimensional scaling analysis (NMDS). As a result, 116 ants morphospecies were collected, distributed in nine subfamilies and 42 genera. No difference was found in species richness of ants between LRs and PPAs and only percentage of canopy cover was significantly different. We also did not find differences of ant assemblages or functional groups between LR and PPA and this fact reinforces that the NCFB is coherent indicating that LR and PPA are similar in maintaining of local biodiversity. Thus, using the PPA in the calculation of LR (or vice versa) does not imply the reduction of local diversity of ants and consequently loss of ecological functions and interactions mediated by species of this group as these areas have similarity in structure and species diversity.